Pavilhão de Bambu Intertwine – Preservação, Inovação e Promoção do Património Imaterial de Macau - Soares, Nuno (2022)

Public Matters: Identity, Design, and Placemaking in Macau’s Inner Harbou - Soares, Nuno (2021)

Reframing the Urban Edge - Design Strategies for Macau x Zhuhai Waterfront - Soares, Nuno (2020)

Cross Border Lab: Reframing the Urban Edge - Macau x Zhuhai - Soares, Nuno (2020)

Local Matters - Design Driven by Urban Conditions [Video] - Soares, Nuno (2020)

A experiência de Macau e Hong Kong – Ensino de Arquitectura entre o Local e o Global - Soares, Nuno (2018)
Keynote Presentation

ASIA URBAN LAB – Comparative Studio - Soares, Nuno (2018)

SHAPED BY USE - Mapping, Debating and Envisioning the Customization of Urban Space - Soares, Nuno (2018)
Keynote Presentation

SHAPED BY USE - Individual designs reshaping the city - Soares, Nuno (2017)
Macau is the most densely populated territory in the world, a small but complex urban landscape populated by a myriad of informal devices that produce a dramatic impact on the image and use of the city, creating an ever-present layer shaped by use. The traditional fields of architectural and urban morphology base their analysis on the private and public space, on the forms of buildings, block, streets, and squares. However, the urban landscape is not only shaped top down by market forces, governments, institutional players, but also bottom-up by thousands of small scale interventions carried out daily by their inhabitants, to solve problems or seize opportunities, on the normal process of usage. This research summarizes an extensive analysis of Macau’s urban landscape focused on this layer of appropriation, aimed to identify these shapes generated by use or, in other words, the devices that materialize the phenomenon of appropriation of the public space. They can take the shape of window cages, rooftop houses, canopies, annexes, hawker booths, and outdoor ads. SHAPED BY USE Individual designs reshaping the city – is a typo morphological essay aimed to provide a methodological tool for the analysis of such phenomena, both in this and other similar urban contexts as well as a compelling starting point to speculate on how small scale individual designs can contribute to reactivate and be harnessed to positively reshape the city.

Comparing Urban Rules for Urbanizing Villages in Hong Kong, Macau, and Shenzhen - Tieben, H.; Chu, J.; Soares, Nuno (2014)